tRNA-Derived Fragment tRF-17-79MP9PP Attenuates Cell Invasion and Migration via THBS1/TGF-β1/Smad3 Axis in Breast Cancer - Mo, Dongping; He, Fang; Zheng, Junyu; Chen, Huanhuan; Tang, Li; Yan, Feng (Frontiers in Oncology, 2021)
tRNA derivatives have been identified as a new kind of potential biomarker for cancer. Previous studies have identified that there were 30 differentially expressed tRNAs derivatives in breast cancer tissue with the high-throughput sequencing technique. This study aimed to investigate the possible biological function and mechanism of tRNA derivatives in breast cancer cells. One such tRF, a 5'- tRF fragment of tRF-17-79MP9PP (tRF-17) was screened in this study, which is processed from the mature tRNA-Val-AAC and tRNA-Val-CAC. tRF-17 with significantly low expression in breast cancer tissues and serum. The level of tRF-17 differentiated breast cancer from healthy controls with sensitivity of 70.4% and specificity of 68.4%. Overexpression of tRF-17 suppressed cells malignant activity. THBS1 (Thrombospondin-1) as a downstream target of tRF-17, and reduction of THBS1 expression also partially recovered the effects of tRF-17 inhibition on breast cancer cell viability, invasion and migration. Besides, THBS1, TGF-β1, Smad3, p-Smad3 and epithelial-to-mesenchymal transition related genes N-cadherin, MMP3, MMP9 were markedly down-regulated in tRF-17 overexpressing cells. Moreover, tRF-17 attenuated the THBS1-mediated TGF-β1/Smad3 signaling pathway in breast cancer cells. In general, the tRF-17/THBS1/TGF-β1/smad3 axis elucidates the molecular mechanism of breast cancer cells invasion and migration and could lead to a potential therapeutic target for breast cancer.